2018
DOI: 10.1038/s41598-018-31408-3
|View full text |Cite
|
Sign up to set email alerts
|

Histamine causes endothelial barrier disruption via Ca2+-mediated RhoA activation and tension at adherens junctions

Abstract: During inflammation, the disruption of the endothelial barrier leads to increased microvascular permeability. Whether tension along cell junctions contributes to histamine-induced endothelial barrier disruption remains unknown. Rapid Ca2+ influx induced by both histamine and thrombin was accompanied by endothelial barrier breakdown revealed as drop of transendothelial electric resistance in primary human microvascular endothelial cells. Interestingly, GLISA measurements revealed activation of RhoA but not inac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 59 publications
(91 reference statements)
3
34
0
Order By: Relevance
“…A recent study implicates the adherens junctions as being pivotal for the histamine‐induced tension of endothelial cells. The proposed mechanism is that the fibres induced to contract by histamine require anchoring to intact adherens junctions to achieve widening of the intercellular cleft . A working hypothesis that may explain previous observations by others as well as the present findings is therefore that histamine acts to widen the clefts between endothelial cells mainly when they have near basal cAMP/Epac1 stimulation.…”
Section: Discussionsupporting
confidence: 76%
“…A recent study implicates the adherens junctions as being pivotal for the histamine‐induced tension of endothelial cells. The proposed mechanism is that the fibres induced to contract by histamine require anchoring to intact adherens junctions to achieve widening of the intercellular cleft . A working hypothesis that may explain previous observations by others as well as the present findings is therefore that histamine acts to widen the clefts between endothelial cells mainly when they have near basal cAMP/Epac1 stimulation.…”
Section: Discussionsupporting
confidence: 76%
“…Although Cav3 knockout mice develop heart failure due to myocardial fibrosis and dilated cardiomyopathy 40 , functions of Cav3 in the peripheral vasculature have not been studied in mice. CTNNA2 / Ctnna2 encodes α-catenin 2, which functions as a linker between cadherin adhesion receptors and the cytoskeleton, and thereby regulates cell-cell adhesion dynamically in response to histamine 41 . However, since genome-wide knockout of Ctnna2 in mice is associated with neonatal lethality, with most homozygotes dying with 24 h after birth 42 , vascular-specific deletion of Ctnna2 may be necessary to interrogate its potential role in Histh and SCLS.…”
Section: Discussionmentioning
confidence: 99%
“…Several compounds have been identified that inhibit ROCK1 activity and might therefore prove effective for treating NSCLC. For example, histamine [ 52 ], fibroblast-derived hepatocyte growth factor [ 53 ], triptolide [ 54 ], and melatonin [ 55 , 56 ] have been used to inhibit ROCK1 activation. However, additional clinical studies and pre-clinical experiments are needed to support the use of these and other compounds as clinically useful targeted therapeutic agents in NSCLC patients.…”
Section: Resultsmentioning
confidence: 99%